Artistic time in D. Keyes’ novel Flowers for Algernon - Antonina V. Samoylova; Olga V. Spachil (RUDN Journal of Studies in Literature and Journalism)
The problems presented in Flowers for Algernon (1966) the novel by American writer Daniel Keyes (1925-2014), fall within the realm of existential questions of the 20th century: the meaning and purpose of human life, family and interpersonal relationships, the place of a deviant personality in society, the ethics of experimental science and medicine, empathy and compassion, and the role of science and knowledge, among others. The novel has been included in lists of the greatest books of our time, has become a modern classic, and the story of the same name from 1959 is mandatory reading for schoolchildren in the USA and Japan. This represents the first study of the category of artistic time in the novel. This consideration is relevant not only due to its significance as one of the main structural elements of the text, but also from the perspective of its importance in constructing an event sequence through the lens of the author’s unique vision and the formation of the intratextual psychomental paradigm of the protagonist. The relevance of the work is further substantiated by the interdisciplinary nature of the study, which combines linguistic and literary criticism approaches, aimed at understanding the functional capabilities of the category of time as a universal tool. This tool plays a key role in works of complex genre, including Keyes’s novel. The study identifies the main guidelines for developing the novel’s temporal structure design: “zero chronotope”, dichotomy “past vs present”, introduction of reminiscences as temporal catalysts of psycho-emotional outbursts and self-reflection. Time serves as the central construct within the text of the novel, intricately weaving together all plot lines and embodying a conceptual framework.